Problems of Teaching and Translation of Medical English to Students of Tertiary Level - Hassoun, Zeinab Isam Ahmed (Advances in Social Sciences Research Journal, 2019)
The researcher intends to investigate the problems that faced teachers and translators of medical English. A sample has been chosen randomly from the population of the study. The researcher used an interview to collect data about the problems of the study. She adopted the descriptive and the analytical methodology to analyze and discuss the results of the interview. The researcher reached some findings and causes of the problems. Also, the researcher recommended some points for recovery.